Association between Nonalcoholic Fatty Liver Disease and Endocrinopathies: Clinical Implications - Ana-Maria Singeap; Carol Stanciu; Laura Huiban; Cristina Maria Muzica; Tudor Cuciureanu; Irina Girleanu; Stefan Chiriac; Sebastian Zenovia; Robert Nastasa; Catalin Sfarti; Camelia Cojocariu; Anca Trifan (Canadian Journal of Gastroenterology and Hepatology)
Nonalcoholic fatty liver disease (NAFLD) has a rising prevalence worldwide. Its potential for evolution towards liver cirrhosis and hepatocellular carcinoma, as well as associations with extrahepatic manifestations, represents a double burden for patients and physicians alike. Recently, there has been increasing evidence of the association between NAFLD and a number of endocrinopathies, such as hypothyroidism, polycystic ovarian syndrome (PCOS), hypopituitarism, growth hormone deficiency (GHD), hypogonadism, and hypercortisolism. Definite correlations are supported by clear evidence so far, but further studies are needed in order to completely clarify the pathogenic mechanisms and, especially, to identify therapeutic implications. In this review, we present the main relationships between NAFLD and endocrinopathies, emphasizing the reciprocal causality, evolutive interconnections, and current clinical scenarios of presentations of which the clinicians should be aware.